Closed Reduction and Percutaneous Pinning in the Treatment of Humeral Distal Metaphyseal-Diaphyseal Junction Fractures in Children: A Technique Note and Preliminary Results - Zhou, Hai; Zhang, Ge; Li, Ming; Liu, Xing; Qu, Xiangyang; Cao, Yujiang; Weng, Liuqi; Zhang, Yuan (Frontiers in Pediatrics, 2021)
Objective The metaphyseal-diaphyseal junction (MDJ) fracture is an uncommon but problematic type of fracture occurring at the distal humerus in children. Closed reduction and fixation are challenging and may not be possible with the conventional reduction maneuver utilized in supracondylar fractures. The purpose of this study was to evaluate a novel closed reduction and percutaneous pinning (CRPP) technique for the treatment of these fractures. Methods We retrospectively evaluated 14 children (8 boys and 6 girls) who underwent closed reduction and percutaneous fixation for the treatment of MDJ fractures. Six children who underwent treatment with a novel CRPP technique were enrolled as Group A. Eight children underwent the conventional reduction maneuver utilized in supracondylar fracture and were enrolled as Group B. Clinical and radiographic outcomes in the two groups were then compared. Results In Group A, all six MDJ fractures were treated successfully with the novel CRPP technique without the need for open procedures or re-operation. No complications such as pin-site infection or iatrogenic nerve injury were found in this group. In group B, five of eight fractures were treated successfully with the conventional CRPP technique, three fractures needed open reduction, and one of them had further surgery because of the loss of fixation. Children with successful CRPP in each group were included to compare the efficacy of the novel CRPP technique. The average duration of the surgery in Group A was significantly shorter than that in Group B (P < 0.001). At last follow up, both groups obtained satisfactory clinical and radiographic outcomes. Conclusion MDJ fractures can be reduced successfully and fixed stably via a novel CRPP technique, and laborious and frustrating attempts at closed reduction and further open reduction can be avoided.